2004
DOI: 10.1136/ebn.7.4.119
|View full text |Cite
|
Sign up to set email alerts
|

Review: prophylactic use of vitamin D reduces falls in older people

Abstract: Study selection and assessment: randomised controlled trials (RCTs) that compared prophylactic use of any type of vitamin D with a control condition in community dwelling or institutionalised older people (mean age of study participants had to be >60 y) and included a methods section that stated how falls (the outcome) were defined and ascertained. Individual study quality was assessed using specified criteria that included allocation concealment, blinding, and withdrawals.Outcomes: low trauma falls defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“… 10 Interestingly, a meta-analysis looking at five randomized controlled trials in prophylactic use of vitamin D in older people showed a decrease in the number of falls in group receiving prophylactic vitamin D with needed to treat =15 (95% CI 9–52). 11 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Interestingly, a meta-analysis looking at five randomized controlled trials in prophylactic use of vitamin D in older people showed a decrease in the number of falls in group receiving prophylactic vitamin D with needed to treat =15 (95% CI 9–52). 11 …”
Section: Discussionmentioning
confidence: 99%